Plan estratégico de marketing para la empresa Taller de pintura Robles - Roblez Pardo, James Alexander (2022)
The objective of implementing a "STRATEGIC MARKETING PLAN FOR THE COMPANY TALLER DE PINTURA ROBLES," is to develop strategies that allow the increase in the customer portfolio for this company; the same that was based on four specific objectives, the first corresponds to perform an internal, external and competition situational diagnosis to identify strengths, opportunities, weaknesses and threats, in the internal diagnosis was built the matrix of internal factors through the information obtained through surveys, interview and direct observation records; In the external diagnosis, a PESTE analysis was carried out to determine the impact of political, economic, social, technological and ecological factors, as well as a study of Porter's 5 forces, which provided a more general overview of the company's current situation. The second objective was based on developing a market study for which a methodology with a non-probabilistic approach was used to collect information to determine tastes, preferences and aptitudes of the company's customers, from which a sample of 306 customers was obtained using a sampling technique by own judgment. The third objective corresponds to designing Marketing Mix strategies which were proposed in relation to the results of the high impact matrix, where each of them could be linked to form the micro and macro strategies which were developed in this work. The fourth and last objective is based on determining the general budget for the execution of the proposed strategies, with a total investment of $1387.50. Finally, once the corresponding research has been carried out, the conclusions and recommendations are presented, as well as the bibliography and the corresponding annexes.